2016
DOI: 10.1055/s-0042-116117
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin, Ghrelin O-Acyltransferase, and Carbohydrate Metabolism During Pregnancy in Calorie-Restricted Mice

Abstract: Acylation of ghrelin is mediated by ghrelin acyltansferase (GOAT). Exogenous acylated ghrelin (AG) stimulates growth hormone (GH) and food intake. In non-pregnant (NP) animals, the GOAT-ghrelin-GH axis prevents hypoglycemia caused by caloric restriction (CR). In humans, maternal malnutrition challenges glucose metabolism, which is a key determinant of fetal health. To clarify the role of AG and GH, we compared effects of CR on the GOAT-ghrelin-GH axis in pregnant (P) and NP mice. C57BL/6 wild type (WT) and GOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Ghrelin exists in two forms: acylated ghrelin (AG) and unacylated ghrelin. O -acyltransferase (GOAT) transfers an acyl group from the fatty acids to the serine-3 residue of ghrelin and, thus, stimulates GH secretion and food intake [ 4 , 5 ]. GOAT activates ghrelin depending on an esterification reaction, and blockade of GOAT activity induces less food intake and weight gain [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin exists in two forms: acylated ghrelin (AG) and unacylated ghrelin. O -acyltransferase (GOAT) transfers an acyl group from the fatty acids to the serine-3 residue of ghrelin and, thus, stimulates GH secretion and food intake [ 4 , 5 ]. GOAT activates ghrelin depending on an esterification reaction, and blockade of GOAT activity induces less food intake and weight gain [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that AG could regulate GOAT expression in the stomach[ 8 ] and that the widespread expression of GOAT corresponded to the widespread distribution of ghrelin expression, e.g ., in the pancreas, stomach and hypothalamus[ 8 , 9 ]. Multiple studies have demonstrated that both ghrelin and GOAT play important roles in the regulation of obesity, blood glucose and insulin[ 5 , 10 , 11 ]. However, it is not clear whether the ghrelin/GOAT axis in the hypothalamus ( via autocrine/paracrine signaling) is involved in the maintenance of blood glucose concentrations and energy homeostasis by restricting food intake after SG.…”
Section: Introductionmentioning
confidence: 99%
“…pituitary ghrelin expression in pregnant and non-pregnant mice reported previously (Trivedi et al 2017). However, the 1.5-fold greater density of ghrelin-positive cells in the stomach antrum of pregnant than non-pregnant mice sampled at ZT13 (study one) suggests a greater capacity to secrete ghrelin, although this was not seen at ZT23 (study two).…”
Section: Journal Of Endocrinologymentioning
confidence: 74%
“…Intravenous administration of exogenous acyl-ghrelin induces GH pulses in humans and rodents (Kojima et al 1999, Arvat et al 2001, while mice deficient in ghrelin or Mboat4 have lower amplitude GH pulses than littermate controls (Hassouna et al 2014, Xie et al 2015. Acyl-ghrelin, but not des-acyl ghrelin, also acts centrally to stimulate food intake (Nakazato et al 2001, Neary et al 2006, and acyl-ghrelin plays an important role in metabolic adaptations to maintain circulating glucose in response to calorie restriction, particularly in pregnancy (Trivedi et al 2017). Although ghrelin and Mboat4 are predominantly expressed in the stomach (Kojima et al 1999), ghrelin, Mboat4 and GHSR expression are also detected in the human (Gnanapavan et al 2002, González-Domínguez et al 2016 and rodent (Gualillo et al 2001, Nonoshita et al 2010 placenta.…”
Section: Introductionmentioning
confidence: 99%